2020
DOI: 10.1021/acs.jpcb.0c00073
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Modulation of Electrical Current through DNA Sequences: Engineering of a Molecular Optical Switch

Abstract: Designing a molecular switch with bistable on/off states is of particular interest in molecular electronics. Motivated by experimental studies of molecular conductors, interplays of photons and electrons and their effects on electrical properties are studied theoretically. We have tried to model a molecular optical switch based on DNA sequences of the hepatitis delta virus and Toxocara canis parasite. The electrical response of chains to the light irradiation was examined to optimize the function of an optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Quite interestingly, the electrical response of biological dsDNA chains to light irradiation has been recently investigated in order to engineer a DNA based molecular switch. In these experiments, it was observed that the electrical current turns on when the frequency of the incident light is above the 2 THz threshold [64], a value that coincides with that listed for ν ϕρ in Table 2. On the other hand, it is worth mentioning that the ν HS frequency value listed in Table 2 is smaller than the 2.83 and 3.04 THz frequencies experimentally observed by optical Kerr-effect spectroscopy in ds-GGCGGCCCGCGCGGGCCGCC and ds-ATTATTATTATATTA oligonucleotides, respectively.…”
Section: Dynamics Of Homopolymer Dsdna Macromoleculessupporting
confidence: 77%
“…Quite interestingly, the electrical response of biological dsDNA chains to light irradiation has been recently investigated in order to engineer a DNA based molecular switch. In these experiments, it was observed that the electrical current turns on when the frequency of the incident light is above the 2 THz threshold [64], a value that coincides with that listed for ν ϕρ in Table 2. On the other hand, it is worth mentioning that the ν HS frequency value listed in Table 2 is smaller than the 2.83 and 3.04 THz frequencies experimentally observed by optical Kerr-effect spectroscopy in ds-GGCGGCCCGCGCGGGCCGCC and ds-ATTATTATTATATTA oligonucleotides, respectively.…”
Section: Dynamics Of Homopolymer Dsdna Macromoleculessupporting
confidence: 77%
“…Since ρ n,n±1 = ρ n ± p n,n±1 = 2ρ n , we see that all the bps in the codon move in phase. A similar solution describing a modulated oscillation in opposite phase is obtained by choosing ρ n = p n,n±1 as the particular solution to the inhomogeneous differential Equation (38). In this case, we get a larger high frequency value γ + = 1.774 THz.…”
Section: Orchestrated Codon Oscillationsmentioning
confidence: 54%
“…For the sake of comparison, the transition times reported for intrastrand hole transfer in ds-GT n GGG oligonucleotides, range from τ = 0.5 ps for n = 1 to τ = 315 ps for n = 4 [37]. Remarkably, recent studies on the electrical response of biological dsDNA chains to light irradiation, performed to engineer a DNA-based molecular switch, have unveiled that electrical current turns on for incident light frequencies above the 2 THz threshold [38], a figure very close to that listed for ν ϕSH in Table 2, a frequency involving energy enough to activate all the fundamental interactions present in the system Hamiltonian in a coupled way.…”
Section: Oscillationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the massive speed-up in processing power that arises from reduced spatial dimensions, molecular junctions can produce a massive speedup in clock speed by harnessing THz intramolecular transport processes [11,12]. The advanced temporal resolution of molecular devices also has applications in frequency doublers and detectors [13,14] and switches for fast memory storage [15][16][17][18]. Experimental advances in miniaturization of integrated devices in electrical circuits, potentially utilizing the nextgeneration nanoscale components operational in the GHz-THz regime, have prompted remarkable interest in the theoretical description of these systems.…”
Section: Introductionmentioning
confidence: 99%